Best Answer

5x - 2 = x + 6 is an equation - a linear equation - in one variable, x.

That answers the question which was asked.

But, perhaps you wanted a solution to the equation but were too embarrassed to ask?

5x - 2 = x + 6

Subtract x from both sides: 4x - 2 = 6

Add 2 to both sides: 4x = 8

Divide both sides by 4: x = 2

Q: What is 5x-2 equals x plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x2-2x+36 = 5x2+10x 6x2-5x2-2x-10x+36 = 0 x2-12x+36 = 0 (x-6)(x-6) = 0 x = 6 or x = 6 It has two equal roots.

Factorise: 5x2 + 2x - 192 = (x - 6)(5x + 32) = 0; whence, x = 6 or -6.4.

X= (3/5 , -2)

for x = -2: x2 = 4, -5x2 = -20; 3x = -6 giving -20 - (-6) = - 20 + 6 = -14.

I am assuming the question is to factor this problem? 5x2 + 29x - 6 (5x - 1)(x + 6)

Related questions

6x2-2x+36 = 5x2+10x 6x2-5x2-2x-10x+36 = 0 x2-12x+36 = 0 (x-6)(x-6) = 0 x = 6 or x = 6 It has two equal roots.

Factorise: 5x2 + 2x - 192 = (x - 6)(5x + 32) = 0; whence, x = 6 or -6.4.

X= (3/5 , -2)

for x = -2: x2 = 4, -5x2 = -20; 3x = -6 giving -20 - (-6) = - 20 + 6 = -14.

(x - 6)(5x - 6)

I am assuming the question is to factor this problem? 5x2 + 29x - 6 (5x - 1)(x + 6)

5x2 + 15x = 0 5x(x + 3) = 0 therefore, x = 0 or x + 3 = 0 that is, x = 0 or x = -3

5x2 + x - 6 = (5x + 6)(x - 1) 5x2 - x - 6 = (5x - 6)(x + 1)

5x2 - 136 = 44 5x2 - 136 + 136 = 44 + 136 5x2 = 180 5x2/5 = 180/5 x2 = 36 âˆšx2 = âˆš36 x = Â±6

5x2 - 16x + 12 = 5x2 - 10x - 6x +12 = 5x(x - 2) - 6(x - 2) = (x - 2)(5x - 6) Whether or not these are in descending order depends on the value of x.

(5x - 6)(x - 2)

Two. x = + i sqrt(8.4) x = - i sqrt(8.4)